SISTEM INFORMASI PEMESANAN FURNITURE DI TOKO ARISTOTLES KABANJAHE BERBASIS WEB - Pilipus Tarigan; Rayna Dara Br Sembiring (UPPM, 2020)
Furniture is a household need that includes all items such as tables, chairs, beds, and cabinets. Furniture is also a life support today which is very popular with the community. Aristotles' shop is a furniture sales business, it is still selling goods from the shop, and the introduction of its products is still home to house. This resulted in prospective buyers still having to leave the house to buy the desired item, by following current technological developments the author built an information system for ordering goods at Aristotles Shop online using the PHP programming language in the process.